Hotate (Patinopecten yessoensis) Seeding Technique using Zabutonkago and Marukago Tools with Hanging Method in Funka Bay Hokkaido, Japan - faza Amalia Khoerunnisa; Petrus Hary Tjahja Soedibya; Iriyama Gyogyo (PT. Artha GenetikaLab Indonesia, 2024)
This research focuses on cultivation techniques for Hotate shellfish (Patinopecten yessoensis) during the hatchery phase in Funka Bay, Hokkaido, Japan. Hotate scallops are also called giant ezo scallops, these scallops are cultivated in Japan because they have relatively high productivity. This research aims to determine the best seeding technique for mussels (Patinopecten yessoensis) using the hanging zabuton-kago and maru-kago media. The research method uses observation and interviews with company owners. The results show that the technique for seeding Hotate shellfish (Patinopecten yessoensis) using pearl nets and lantern nets from May to September was carried out in 3 processes, namely chigai, kari-bunsan, and hon-bunsan. The method used is to sort the shells repeatedly until they reach a size of 50 mm – 70 mm during the mimizuri process in March. The hatchery process for cultivating Hotate shellfish can provide the basis for valuable information for sustainable management and maintenance in the future.